1991
DOI: 10.1007/bf00317605
|View full text |Cite
|
Sign up to set email alerts
|

Growth and photosynthetic response of nine tropical species with long-term exposure to elevated carbon dioxide

Abstract: Seedlings of nine tropical species varying in growth and carbon metabolism were exposed to twice the current atmospheric level of CO for a 3 month period on Barro Colorado Island, Panama. A doubling of the CO concentration resulted in increases in photosynthesis and greater water use efficiency (WUE) for all species possessing C metabolism, when compared to the ambient condition. No desensitization of photosynthesis to increased CO was observed during the 3 month period. Significant increases in total plant dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
2
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(94 citation statements)
references
References 18 publications
8
80
2
4
Order By: Relevance
“…Small, or no change in biomass accumulation under elevated CO 2 conditions was also observed in ®eld experiments with Populus (Ceulemans and Mousseau 1994), in natural grassland (SchaÈ ppi and KoÈ rner 1996), and temperate forest communities (Cipollini et al 1993). These studies are in contrast to results of studies with tropical plants in pots (e.g., Oberbauer et al 1985;Hogan et al 1991;Ziska et al 1991;Winter and Lovelock, in press), and also to studies of other natural (e.g., Drake 1992;Norby et al 1992;WuÈ rth et al, in press ) and managed (e.g., Idso et al 1991) ecosystems, all of which have shown enhancements in productivity under elevated CO 2 . One explanation as to why plants in some experiments do not show enhancements in productivity under elevated CO 2 is that resources other than carbon are limiting growth under elevated CO 2 (KoÈ rner 1993).…”
Section: A1mentioning
confidence: 82%
See 2 more Smart Citations
“…Small, or no change in biomass accumulation under elevated CO 2 conditions was also observed in ®eld experiments with Populus (Ceulemans and Mousseau 1994), in natural grassland (SchaÈ ppi and KoÈ rner 1996), and temperate forest communities (Cipollini et al 1993). These studies are in contrast to results of studies with tropical plants in pots (e.g., Oberbauer et al 1985;Hogan et al 1991;Ziska et al 1991;Winter and Lovelock, in press), and also to studies of other natural (e.g., Drake 1992;Norby et al 1992;WuÈ rth et al, in press ) and managed (e.g., Idso et al 1991) ecosystems, all of which have shown enhancements in productivity under elevated CO 2 . One explanation as to why plants in some experiments do not show enhancements in productivity under elevated CO 2 is that resources other than carbon are limiting growth under elevated CO 2 (KoÈ rner 1993).…”
Section: A1mentioning
confidence: 82%
“…Experiments assessing the in¯uence of elevated CO 2 on the productivity of plant species from tropical ecosystems have shown con¯icting results. Plants grown individually in pots have shown increases in biomass accumulation when kept under elevated CO 2 (Oberbauer et al 1985;Ziska et al 1991;Winter and Lovelock, in press), while those in experiments where plants have been grown in competing arrays (Reekie and Bazzaz 1989), or in glasshouse-maintained micro-ecosystems (KoÈ rner and Arnone 1992; Arnone and KoÈ rner 1995) have shown very little increase in biomass accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu (1995) and Zhu, Bartholomew & Goldstein (1997) obtained significant increases in total plant dry mass of A. comosus grown at elevated CO 2 in two separate studies. We attribute the lack of a CO 2 response in the study of Ziska et al (1991) to waterlogging due to twice-daily watering of pots to saturation. Waterlogging of A. comosus rapidly damped the diurnal change in leaf titratable acidity and reduced growth (Min 1995 (Winter & Engelbrecht 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the tussock tundra dominated by E. vaginatum, Tissue & Oechel (1987) reported photosynthetic capacity completely acclimated to elevated CO 2 treatment within 3 weeks, after which plants grown at 660cm 3 m-3 had the same rate of photosynthesis as those grown and tested at 330cm 3 m-3 • But not all studies of plants acclimating to elevated CO 2 have shown reduced capacity for photosynthesis. Some studies have reported either an increase or no change in photosynthetic capacity of elevated CO 2 Conroy, 1989;Du Cloux et al, 1989;Hollinger, 1987;Radin et al, 1987;Valle et al, 1985;Ziska et al, 1991). See also the paper by W. Arp in this issue (pp.…”
Section: Introductionmentioning
confidence: 97%